2018
DOI: 10.1016/j.phrs.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Lipid pathway deregulation in advanced prostate cancer

Abstract: The link between prostate cancer (PC) development and lipid metabolism is well established, with AR intimately involved in a number of lipogenic processes involving SREBP1, PPARG, FASN, ACC, ACLY and SCD1. Recently, there is growing evidence implicating the role of obesity and peri-prostatic adipose tissue (PPAT) in PC aggressiveness and related mortality, suggesting the importance of lipid pathways in both localised and disseminated disease. A number of promising agents are in development to target the lipoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 108 publications
(95 reference statements)
1
83
1
1
Order By: Relevance
“…MUFAs are the main contributor to total membrane phospholipids and cholesterol esters. Pharmacological inhibition of SCD1 reduces lipid and MUFAs synthesis, suggesting that SCD1 is a master regulator of membrane composition [21]. This fact points out that SCD1 is a central element of lipid metabolism and body weight control [14].…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 99%
See 3 more Smart Citations
“…MUFAs are the main contributor to total membrane phospholipids and cholesterol esters. Pharmacological inhibition of SCD1 reduces lipid and MUFAs synthesis, suggesting that SCD1 is a master regulator of membrane composition [21]. This fact points out that SCD1 is a central element of lipid metabolism and body weight control [14].…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 99%
“…SREBP1 is the master regulator in fatty acid metabolism, and its activation has been linked to obesity, fatty liver disease, insulin resistance, autoimmune diseases, as well as cancer development. SREBP1 controls SCD1 expression [21,26], and therefore factors activating SREBP1 signaling, such as Inflammatory pathway is shown in green. SCD1 inhibition reduces the pro-inflammatory environment and nuclear factor kappa-B (NFκB) signaling to reduce cell proliferation, while NFκB signaling activation promotes transcription factors binding to SCD1 promotor and gene expression.…”
Section: Stearoyl-coa Desaturase (Scd)mentioning
confidence: 99%
See 2 more Smart Citations
“…As such, cellular metabolic disorders are a hallmark of cancer . FASN is critical for maintaining lipid homeostasis in PCa . Recent systematic sequencing studies revealed that recurrent somatic mutations are key features of PCa, and SPOP was the most commonly mutated gene .…”
Section: Discussionmentioning
confidence: 99%